The Path to Socialism: The Program for Fostering Cooperatives and Socializing Public System - Wolski, Jan (Praktyka Teoretyczna, 2018)
The paper by Jan Wolski — a Polish theoretician and cooperative activist — constitutes the third section of the book Spółdzielczy samorząd pracy [Cooperative Labour Self-Management], which he wrote over the years of 1943-1956, but which was never published as a whole. The manuscript, from the author’s family archives, includes the information that this piece was ―written in 1943 for the Inter-union Cooperative Committee (functioning underground in Warsaw during II World War) and the Socialist Planning Commission‖. Entitled Cooperative Labour Self-Management, this section of the planned book was published in the monthly magazine Więź [Bond], issue no. 2 of 1972, and in 2011 on the website Lewicowo.pl. It contains Wolski’s deliberations regarding the functioning of cooperative labour self-management under the conditions of a social and economic transformation heading towards a classless society. Wolski believed a universal labour-based political system to be one of the essential conditions of socialism, supplanting the old organisational forms originating from the capitalist period. As such, universal labour self-management together with other forms of popular self-government, and particularly user self-government, constitutes a transmission belt between the populace’s grassroots activity and top-down political organisation. Mindful of Edward Abramowski’s teachings, Wolski considered that only having the state based on self-governing cooperative institutions consisted the true realisation of universal will, and thereby the realisation of socialist ideals.